The use of a hematology analyzer with a new generation of software as an alternative to flow cytometry for enumerating residual white blood cells in blood components. Issue 1 (26th November 2019) - Blanco, Richard Alejo; Cavagnetto, Chloe; Willmott, Laura; Aydogdu, Elif; Akinyemi, Nicola; Standring, Helena; Procter, Simon; Garner, Stephen F.; Shirakami, Atsushi; Saker, Jarob; Linssen, Joachim; Cardigan, Rebecca
Abstract : BACKGROUND: Leukoreduction of blood components was implemented to reduce transfusion‐associated risks. The detection level for residual white blood cells (rWBCs) required to demonstrate leukoreduction was originally considered too low for hematology analyzers. Developments enabling cell counts in body fluids have, however, renewed interest in rWBC counting. An assessment of Sysmex XN hematology analyzers with software offering automated rWBC enumeration intended for use on blood components was performed. STUDY DESIGN AND METHODS: Performance characteristics were determined using platelet, red blood cell (RBC), and plasma samples spiked with WBCs. Subsequently, components (platelets, n = 1367; and plasma, n = 80) were tested and results compared with flow cytometry, to monitor leukoreduction efficiency to a level of less than 1 × 10 6 /unit. Components identified by flow cytometry as having poor leukoreduction, exceeding this limit, were also tested (platelets, n = 3; and RBCs, n = 10). RESULTS: Linearity studies up to 32 WBCs/μL showed good correlation between observed and expected results (R 2 > 0.9996). Precision analysis gave an average limit of quantitation of 2 WBCs/μL with coefficients of variation less than 20%. Average carryover was 0.1%. Plain sample tubes were a source of aberrant results with routine components. Using ethylenediaminetetraacetic acid tubes the analyzer gave results greater than 1 × 10 6 /unit in 2.7% of cases compared with 1.4% by flow cytometry, but overall results were within specification, with more than 90% of components having rWBC values below the limit. All incidences of poor leukoreduction, with flow cytometry results greater than 13 rWBCs/μL were correctly identified, with an excellent correlation between results (R 2 = 0.9818). CONCLUSION: The analyzer demonstrated acceptable performance characteristics for enumeration of rWBCs; consequently, additional multisite evaluations are warranted. Abstract : See article on page 4–6,  in this issue